Dispersal of the delayed action insecticide sulfluramid in colonies of the leaf-cutting ant Atta sexdens rubropilosa (Hymenoptera: Formicidae) - Forti, Luiz C.; Pretto, Dênis R.; Nagamoto, Nilson S.; Padovani, Carlos R. [UNESP]; Camargo, Roberto S.; Andrade, Ana Paula P. (My University, 2007)
Toxic baits are the most used control method for leaf-cutting ants due to their high effectiveness and because they are considered the safest for humans. Taking into account that the importance of leaf-cutting ants as pests, knowing the process by which dispersal and worker contamination is achieved becomes essential to understand several aspects about the functioning of a bait-borne AI (active ingredient) used in toxic baits. It has been established that an effective toxic bait should have a delayed- action AI, but its dispersion among the different sizes of workers is unknown. Workers of different sizes are involved in quite different tasks such foraging, cultivation of symbiotic macrofungus or control of deleterious microfungi. Therefore, we prepared a toxic bait containing the delayed-action AI sulfluramid and a dye (Rhodamine B) as an AI tracer in order to study dispersal and contamination in colonies, evaluated at different periods and in relation to different workers' sizes. Both field and laboratory colonies were evaluated. The great level of contamination, about 50% at 24 hours, in all sizes of workers demonstrates that worker contact with toxic bait is intense within this period. The distribution in field and laboratory colonies was similar. This contamination pattern is probably enough to cause the colony to die because of contamination of smaller workers, leading to the loss of control of the aggressive microfungi, which can quickly overgrow the symbiotic fungus culture. The dispersal dynamics of AI in leaf-cutting ant workers is important for investigations on the mode of action of this insecticide in the colony, and as a reference in future studies, such as those attempting to reduce the concentration of AIs in baits to reduce their environmental impact, or for facilitation of new AI screening.
Keywords: Atta sexdens rubropilosa; Insecticide; Leaf-cuttingant; Rhodamine B; Toxic bait; Atta; Formicidae; Fungi; Hymenoptera